Beyond Competence: Perspectives From Two Centuries. Issue 3 (July 2017) - George, Reena; Narayanan, Kumar
A sense of failure and guilt can often be associated with the death of a patient. Using the Serenity Prayer as a framework, we present autobiographical narratives describing encounters that happened in Vellore, India over a hundred years apart. Powerlessness in the face of death, we suggest, is not the same as ignorance or incompetence. It could well be the breakthrough to a deeper wisdom and lasting empowerment.